IDENTIFIKASI POTENSI PLTMH DI DESA MONGIILO PROVINSI GORONTALO - Komang Arya Utama (TEKNISIA, 2015)
Mongiilo is a village that has a very poor service in electricity supply. However, this village has Butaiyo Kiki River that flows throughout the year that can be used to supply additional power to the community. This research aims to determine the potential of PLTMH from Butaiyo Kiki River in order to solve the problems of electric energy in the village Mongiilo. The method used are observation and measurement directly in the field; determine the dependable discharge by using FJ Mock formula; and analysis of intake infrastructure according to the manual book of  the Directorate General of Irrigation Department of Public Works. The result of this research shows that the average dependable discharge of Q90 obtained at 0.60 m3/sec. Based on conditions on the field site, the height of potential head which is 13.23 m which will generate power of 48,798 Watts. The number of homes receiving electrical power supply with a minimum requirement of electricity per home of 450 watts is 108 Houses. As for the design of building power plants is obtained; weir crest height is 2.5 m, intake geometry are 1 m of  width and 0.5 m of height. Headrace is a rectangle with a height of 1.3 m, a width of 1 m, stilling basin with a width of 1.5 m, length 16 m and height of 2.1 m, sand trap with 0.691 m high and 0.5 m wide with a slope 3.6%; forebay is 6 m long, 3 m wide, height is 2.5 m.